Thumb carpometacarpal joint osteoarthritis: Is there a role for denervation? A systematic review. Issue 7 (July 2020) - Teo, Isabel; Riley, Nicholas
Summary: Thumb carpometacarpal osteoarthritis (CMCJ OA) is a common problem. Joint denervation presents a number of theoretical advantages over more traditional surgical options; it is minimally invasive, it does not require a prosthesis or postoperative immobilisation, and does not preclude future surgery. It can be of particular benefit in patients who require good range of motion which other forms of surgery may compromise. Despite these potential advantages, selective denervation of the thumb CMCJ is not considered as part of the routine surgical armamentarium for the treatment of thumb base OA. The purpose of this study is to analyse the evidence for thumb CMCJ denervation; evaluating patient selection, surgical techniques, complications and outcomes. A systematic review was performed on all published literature relating to thumb CMCJ denervation. Nine studies were identified with 184 denervation procedures undertaken in 175 patients. The length of follow-up was available in eight studies (mean 36.5 months [range 6–152 months]). All authors reported improvement in pain and seven studies reported improvement in function. Eleven patients in total suffered persistent joint pain, ten of which proceeded to trapeziectomy and one patient underwent a revision denervation to address potentially missed dorsal sensory branches. The overall complication rate was 11.4% (0–27.5%) consisting of minor complications. This review highlights the paucity of high-quality data and the requirement for a multi-centre, randomised study with validated outcome measures to further define the role of denervation in the management of thumb base OA.